MODIFIKASI ALGORITMA PLAYFAIR CIPHER DENGAN PENGURUTAN ARRAY PADA MATRIKS - Mhd. Zulfansyuri Siambaton; Abdullah Muhazir (Universitas Islam Negeri Sumatera Utara, 2018)
Playfair Cipher method is one of cryptography method that has long been known and still used until now. But the cryptanalysts are trying to solve the method so it is necessary to modify the Playfair Cipher in order to increase the ability of the security provided. By changing the size of the matrix to 6x6 by adding characters from 0 to 9 and sorting by array into insertion into the matrix, it is expected to be stronger than the standard playfair.